Maize and the Green Revolution: Guatemala in the Global Context of Agricultural Research, 1954–1964 - Méndez Rojas, Diana Alejandra (Ciencia Nueva, revista de Historia y Política, 2019)
This article presents the results of an investigation whose objective was to establish the international links that Guatemala formed with diverse latitudes of the globe, for the purpose of applied scientific research into maize from 1954 to 1964, a period marked by the advancement of the green revolution in Central America. From a global history perspective, the study of the green revolution will be addressed as a process which involved the articulation of networks conformed through the circulation of specialists, civil servants and students, as well as the exchange of knowledge and agricultural materials. The sources used include a specialized bibliography and archive documents.